Severobaikalsk. Returning water to the people - Taam, Artur (project baikal, 2024)
A key point in the Baikal-Amur Mainline (BAM) railway, the northernmost inhabited town by Lake Baikal and a paradoxical amalgamation of intertwined urban challenges, Severobaikalsk is once again undergoing a transformative phase. Expansions of the BAM have breathed new life into the city, creating jobs and growth. In 2022, the local government started the development of a new master plan. REZEDA Studio has joined as a co-author. This article explores the solutions integrated into the final project, challenges faced by our team of developers, how the new master plan will benefit the city, and if Baikal will become a part of the city’s new life.
Keywords: Severobaikalsk; urban planning; master plan; pedestrian bridge